2011
DOI: 10.1007/s10648-011-9174-7
|View full text |Cite
|
Sign up to set email alerts
|

Expertise Differences in the Comprehension of Visualizations: a Meta-Analysis of Eye-Tracking Research in Professional Domains

Abstract: This meta-analysis integrates 296 effect sizes reported in eye-tracking research on expertise differences in the comprehension of visualizations. Three theories were evaluated: Ericsson and Kintsch's (Psychol Rev 102:211-245, 1995) theory of long-term working memory, Haider and Frensch's (J Exp Psychol Learn Mem Cognit 25:172-190, 1999) information-reduction hypothesis, and the holistic model of image perception of Kundel et al. (Radiology 242:396-402, 2007). Eye movement and performance data were cumulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
475
6
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(527 citation statements)
references
References 99 publications
32
475
6
14
Order By: Relevance
“…In the field of eye tracking there are many definitions for fixations, which may differ from Bpauses over informative regions of interest^ (Salvucci & Goldberg, 2000) to BMiniature eye movements that relatively stabilize the retina for a prolonged posture of the eyes over an object^ (Gegenfurtner, Lehtinen, & Säljö, 2011). There is not one simple definition for a fixation; some definitions are formulated as a combination of properties (duration, frequency, amount of small movements), some are functional (e.g., to help perception) or are formulated as a recipe to detect fixations.…”
Section: Labels and The Role Of Instructions And Event Selection Rulesmentioning
confidence: 99%
“…In the field of eye tracking there are many definitions for fixations, which may differ from Bpauses over informative regions of interest^ (Salvucci & Goldberg, 2000) to BMiniature eye movements that relatively stabilize the retina for a prolonged posture of the eyes over an object^ (Gegenfurtner, Lehtinen, & Säljö, 2011). There is not one simple definition for a fixation; some definitions are formulated as a combination of properties (duration, frequency, amount of small movements), some are functional (e.g., to help perception) or are formulated as a recipe to detect fixations.…”
Section: Labels and The Role Of Instructions And Event Selection Rulesmentioning
confidence: 99%
“…In their review of eye-tracking research in various domains (such as radiology, car driving, sports, and chess), Gegenfurtner and his colleagues [31] concluded that experts (compared to less experienced professionals) have, in general, shorter fixation durations during the comprehension of visualizations. This echoes Fitts' previous conclusion about experienced pilots and their shorter fixation durations [23].…”
Section: Stage I: Pilot Training/flight Performance Analysismentioning
confidence: 99%
“…Crucially, however, it is our experience with specific scenes and objects that allows initial scene processing to be exploited, for subsequent eye movements to be guided more effectively towards task relevant areas, and for decisions to be made faster as a function of expertise (Gegenfurtner, Lehtinen, & Säljö, 2011;Reingold & Sheridan, 2011).…”
Section: Introductionmentioning
confidence: 99%